Estimation of Carbon and Biomass Energy Loss Along Shoghi-Shimla- Dhali Bypass in Mashobra Range, Himachal Pradesh - Banyal, Shelly; Aggarwal, Rajeev Kumar; Bhardwaj, Satish Kumar; Sharma, Anju (International Journal of Bio-resource and Stress Management, 2022)
The present study was conducted during 2018−2019 to estimate biomass, carbon storage, CO2 sequestration rate, CO2 mitigation potential and biomass energy of dominant tree species like Pinus roxburghaii, Quercus oblongata, Cedrus deodara, Pinus wallichiana grown along the National Highway-22 (Shoghi−Shimla−Dhali) bypass, Himachal Pradesh, India. Present investigation was carried out by non-destructive method. About 13,967 trees were cut down during road expansion along National Highway-22. The trees Pinus roxburghaii was 64.73%, 74.22% for Quercus oblongata, 73.27% for broad leaves, 53.64% for Cedrus deodara and 51.86% for Pinus wallichiana under class (10_20 cm dbh). The maximum biomass of 2205.3 t ha-1 was observed for Quercus oblongata. Total carbon ranged from 139.26 t ha-1 to 1102.61 for diameter class 10−19 cm dbh to IE>100 cm dbh. The total carbon sequestered rate was found to be 10,306.57 t ha-1. The total CO2 mitigated potential was estimated to be 7498.24 t ha-1 with average biomass energy of 4319.88 t oil equivalent. The study revealed that Quercus oblongata was the major contributor to the total carbon loss and has highest proportion of 39.36% among all species.